The role of athletes' pain-related anxiety in pain-related attentional processes - Bardel, M.-H.; Woodman, T.; Perreaut-Pierre, E.; Barizien, N. (Anxiety, Stress and Coping, 2013)
Numerous researchers have highlighted the social determinants of athletes' attitude toward pain, yet little is known about the role of cognitive processes and emotions that are related to pain in sport endeavors. There is evidence, in a dot probe paradigm, that individuals with chronic pain selectively orient their attention toward pain-related stimuli, but no studies have differentiated between the two attentional processes of hypervigilance that are evident in athletes: facilitated detection of threat and difficulty in disengaging attention from threatening stimuli. In the present study using a dot probe paradigm, we examined whether professional rugby players (N=58) with high pain-related anxiety (HPA) would show an attentional bias for pain-related threat, and whether this hypervigilance would reflect difficulty disengaging from threat or facilitated detection of threat. Rugby players with HPA oriented their attention toward pain-related threat with a concomitant difficulty disengaging from threat. Difficulty disengaging from painful stimuli may increase anxiety, and thus be maladaptive in sport. This is the first study to identify pain-related anxiety as a vulnerability marker in athletes' attentional biases.